Critical policy scholarship in education: An overview - Tebeje Molla (Arizona State University, 2021)
This paper presents an overview of critical policy scholarship (CPS) in education. Historically, policy research has been dominated by what is commonly referred to as the policy science tradition, which is positivist in its philosophical stance and instrumentalist in its purpose-it focuses on producing knowledge relevant for policy decisions. However, with the rise of interpretive social inquiry in the 1970s and against the backdrop of unique political developments in the 1980s, CPS emerged as an alternative policy research perspective. This review discusses the scope and foci of CPS in education under four themes: methodological assumptions, interdisciplinary roots, enduring analytical goals, and emerging empirical contexts. Implications of the prevalence of inequality, Big Data and digital panopticon for educational policymaking and policy research are also briefly discussed. The paper concludes that although its foci of analysis have shifted considerably in the last four decades, analytical interest and tools of CPS remain largely unchanged.